Seasons of Change : Labor, Treaty Rights, and Ojibwe Nationhood - Norrgard, Chantal (Book collections on Project MUSE., 2015)
Between the 1870s and the 1930s, the Lake Superior Ojibwe negotiated dramatic economic, political, and social changes. Spanning that period, which began with the tribe's removal to reservations and closed with the Indian New Deal, this book explores the critical relationship between Ojibwe sovereignty and labour.